Transformasi Perpustakaan dalam Peran Tranmisi Ilmu Pengetahuan Siswa di MTS Darul Falah - Moh. Rafiuddin; Maimun Maimun (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to theoretically describe the transformation of libraries in the transmission of knowledge. By using the library study method, this research is expected to be able to provide a detailed explanation of the research objectives. The results of this research are that the transformation of libraries into science programs involves several important stages, starting from identifying library needs which focus on work program methods that are in accordance with the potential of learning resources in the community as well as the benefits of libraries in the transmission of knowledge to finding out libraries in the development of Islamic science in held in several institutions